Integration of Islamic values in iium:The case of social sciences - Md. Noon, Hazizan (2015)
This presentation outlines some reflections on the main questions regarding integration of Islamic values in human knowledge/sciences and academic curriculum namely the WHY (reason), the WHAT (meaning & concept) and the HOW (implementation). Particular emphasis is given to Integration of Islamic values in Social sciences and curriculum in IIUM